A consistency-based approach to multiple attribute decision making with preference information on alternatives. (May 2018) - Liang, Haiming; Gong, Qiang; Dong, Yucheng; Ding, Zhaogang
Highlights: We propose an approach to avoid the inconsistent rankings of alternatives. We define the geometry consistency index in the MADM problems. We propose the feedback adjustment to improve the defined geometry consistency index. We discuss the properties of the proposed approach by simulation experiments. Abstract: The methodology to solve the multiple attribute decision making (MADM) with preference information on alternatives has been systematically investigated. However, the inconsistency issue between the two rankings respectively derived from the preference information and the decision matrix is seldom considered. In order to investigate this issue, this paper proposes a consistency-based approach to MADM with preference information on alternatives. Based on the classical idea of the geometric consistency index in the preference relation, we define a geometric consistency index in MADM. Then, we propose an algorithm to adjust the preference information and the decision matrix simultaneously to improve the geometric consistency index in MADM. Next, some simulations experiments are designed to discuss the properties of the proposed approach. Finally, through illustrative examples and a comparative analysis, we demonstrate the effectiveness of the proposed approach.